2022
DOI: 10.3390/foods11131898
|View full text |Cite
|
Sign up to set email alerts
|

Organoleptic Chemical Markers of Serpa PDO Cheese Specificity

Abstract: Serpa is a protected designation of origin cheese produced with a vegetable coagulant (Cynara cardunculus L.) and raw ovine milk. Despite the unique sensory profile of raw milk cheeses, numerous parameters influence their sensory properties and safety. To protect the Serpa cheese quality and contribute to unifying their distinctive features, some rheologic and physicochemical parameters of cheeses from four PDO producers, in distinct seasons and with different sensory scores, were monitored. The results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…The inoculation of adjunct cultures is rather common in industrial cheese manufacture to accelerate the ripening process; however, it has an impact on FAA composition [27]. Correlations existing between cheese microbiota and specific FAAs have been highlighted by several authors [28][29][30]. In a previous study, it was demonstrated that in GP cheeses intentionally contaminated with Clostridium tyrobutyricum, the main species responsible for the so called "late blowing" defect in hard cheeses, high contents of free R REVIEW 2 of 10 investigated approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculation of adjunct cultures is rather common in industrial cheese manufacture to accelerate the ripening process; however, it has an impact on FAA composition [27]. Correlations existing between cheese microbiota and specific FAAs have been highlighted by several authors [28][29][30]. In a previous study, it was demonstrated that in GP cheeses intentionally contaminated with Clostridium tyrobutyricum, the main species responsible for the so called "late blowing" defect in hard cheeses, high contents of free R REVIEW 2 of 10 investigated approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In these last cases, poor accuracy in grated cheese mixing before filling the packages can be hypothesized. Indeed, due to the lower water content in the outermost part of the cheese [26,30], grated rind normally contains fibrous particles that tend to separate from the rest of the mix. In a recent study of grated Parmigiano Reggiano cheese, the effect of using different grater types, i.e., drum grater or knife mill, was evaluated [40].…”
Section: Discussionmentioning
confidence: 99%
“…For FAA analysis, the Pico-Tag™ method [37] was used with some adjustments, as described by Araújo-Rodrigues et al [31]. In the first phase, deproteinization and FFA extraction were carried out, homogenizing each cheese model with perchloric acid (0.6 N; 1:10) in an Ultra-turrax ® (T18, IKA) for 2 min at 12,000 rpm.…”
Section: Free Amino Acid (Faa) Profilementioning
confidence: 99%
“…Headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography and mass spectrometry (GC-MS) was used to determine the VFA present in cheese models according to the conditions described by Araújo-Rodrigues et al [31]. For the experiment, flasks of 20 mL (capped with a gastight seal) were used, adding 1 g of each cheese-like model and 10 µL of internal standard (50 mg L −1 of 3-octanol).…”
Section: Volatiles Fatty Acids (Vfa) Profilementioning
confidence: 99%
See 1 more Smart Citation